INTERAKSI NANO-INFLUENCER DAN CUSTOMER EXPERIENCE DALAM MEMBANGUN LOYALITAS KONSUMEN: PERAN MEDIASI KEPUASAN KONSUMEN PADA PRODUK MAKANAN DI KOTA MEDAN - Rizqiya, Fadia Agnil; Nasution, Eri Yanti (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
this study is to determine and analyze the effect of Nano Influencer Interaction and Customer Experience on Consumer Loyalty through Consumer Satisfaction, both directly and indirectly. The approach used in this study is an associative approach. The population in this study were all students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara who purchased food products promoted through Nano Influencer content on social media. The sample in this study used the Lemeshow formula, resulting in 96 students of the Faculty of Economics and Business, Muhammadiyah University of North Sumatra, and the products analyzed were food products promoted through Nano Influencer content on social media. The data collection technique in this study employed a questionnaire. The data analysis technique employed a quantitative approach, employing statistical analysis using the Automated Model Analysis, Inner Model Analysis, and Hypothesis Testing. The data processing in this study used PLS (Partial Least Squares) software. The results of this study demonstrate that direct interaction between Nano Influencers, Customer Experience, and customer satisfaction significantly influence consumer loyalty. Nano Influencer Interaction and Customer Experience significantly influence consumer satisfaction. Meanwhile, indirectly, interaction between Nano Influencers and Customer Experience significantly influences consumer loyalty through consumer satisfaction.